Mathematical Models of Throttle Elements of Gas-hydrodynamic Measuring Transducers - Yevhen Pistun; Halyna Matiko; Hanna Krykh (Energy Engineering and Control Systems)
This is a review article and it presents the flowrate characteristics of throttle elements used for measuring diagrams of transducers of fluids parameters. The review includes a wide range of research on the characteristics of incompressible and compressible fluids, Newtonian and Non-Newtonian fluids at the conditions of laminar, transient and turbulent flow through the channels of different cross-sections. The article considers equations for macroscopic flows. The theoretical equations for calculating the pressure drop for fluid flow in microchannels are presented. The conditions and the range of their application are presented for these equations. The results of experimental research of friction factor for compressible and incompressible fluids in microchannels of various sizes and shapes with smooth and rough surfaces are considered. The obtained results can be used for computer research of static and metrological characteristics of gas-hydrodynamic measuring transducers of specific physical and mechanical parameters of fluids.